Immediate Effects and Short-Term Persistence of an External Focus Instruction During a Rocker-Board Balance Task in Healthy Adults: An Exploratory Randomized Controlled Study - Canan Yuksel-Haji (European Journal of Multidisciplinary Health Sciences, 2026)
Background: External-focus instructions may support more automatic motor control, but their effects appear to vary according to the task, performer and comparison condition. Evidence from balance studies has frequently been based on comparisons with internal-focus instructions, leaving uncertainty about whether an external-focus cue provides an advantage over performing a task without a prescribed attentional strategy. Objective: To examine the immediate effect of a single external-focus instruction on rocker-board balance performance in healthy adults and whether any response remained evident during a subsequent trial after withdrawal of the instruction. Methods: Twenty healthy adults were randomised to an external-focus instruction group or a no-prescribed-focus control group. Participants completed three 30-second rocker-board trials: baseline, an instructed trial and a post-instruction trial. During the instructed trial, the instruction group was asked to minimise rocker-board movement, whereas the control group received no attentional-focus cue. Centre-of-pressure displacement, right-ankle angular motion and rocker-board tilt were analysed using linear mixed-effects models. Prespecified between-group difference-in-change contrasts assessed the immediate and subsequent responses. Results: No significant group-by-trial interactions were identified for centre-of-pressure displacement, ankle movement variability or excursion, or rocker-board movement magnitude. The only significant prespecified contrast concerned the Trial 2-to-post-instruction change in mean rocker-board tilt; however, this outcome represented average board orientation rather than movement magnitude and was not accompanied by corresponding changes in the other biomechanical outcomes. Confidence intervals around several estimates were wide. Conclusion: A single external-focus instruction did not produce a clearly distinguishable immediate or short-term response from completing the rocker-board task without a prescribed attentional-focus cue. The findings suggest that an explicit external cue may provide limited additional information when the task goal is already apparent, although small effects cannot be excluded. Larger studies incorporating manipulation checks and repeated-practice, retention and transfer assessments are required.